Kansas State University Feedlot Boot Camp and Teaching Program: Growing Student Interest and Engagement in the Feedlot Industry - Danielle M. Stock; Pete Anderson; Karol E. Fike (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:Our objectives were to summarize the development and structure of the Kansas State University Feedlot Boot Camp and Teaching Program and examine student interest in careers in the feedlot industry after participation. Study Description:Since 2019, 95 Kansas State University College of Agriculture undergraduate students participated in the Feedlot Boot Camp Program. The aim was to develop students’ knowledge, skills, and professional relationships in feedlot management to help meet the critical need for trained professionals in the industry. Components are a four-day Feedlot Boot Camp, student presentations, animal health day, and an optional feedlot internship. Students who completed all components earned a 2,500 scholarship. Results:A total of 163 undergraduate students applied to participate in the program in its first five years. Of those applicants, 95 were selected to participate in the Feedlot Boot Camp Program. In surveys following the completion of the Boot Camp portion of the program, over 96% (91/95) of student participants agreed with the statement, “My interest in pursuing an internship and (or) career in the feedlot industry grew as a result of this Boot Camp.” Approximately 45% of participants proceeded to participate in feedlot internships or entered full-time jobs working in a feedlot six months after completing the Boot Camp. The Bottom Line:The Feedlot Boot Camp program has made progress in growing student interest and awareness of career opportunities in the feedlot industry and fostering communication between employers and prospective employees.
Keywords: feedlot; internship; career